ConVarT: Search Engine for Missense Variants Between Humans and Other Organisms. Issue 11 (22nd November 2022) - Pir, Mustafa S.; Cevik, Sebiha; Kaplan, Oktay I.
Abstract: ConVarT (https://convart.org/ ) is a search engine for searching for conjugate variants between humans and other species. The search engine is based on matching conjugate variants called MatchVars between species. Matching equivalent variants requires correct alignment of orthologous proteins with the use of multiple sequence alignments (MSA). Indeed, the ConVarT pipeline has performed over a million MSAs and integrated variants and variant‐specific annotations (pathogenicity, phenotypic variants; etc.) into the corresponding positions on MSAs. When a clinically relevant variant is discovered whose functional relevance is unknown, ConVarT offers clinician scientists the possibility to search for a MatchVar in other species and to look for functional data on that variant. Fortunately, ConVarT enables users to paste a protein sequence in FASTA format to search for human orthologous proteins. A pairwise sequence alignment (PSA) is then performed between the provided protein sequence and the human orthologous protein, allowing users to visualize human variants on the PSA. Here, we describe the step‐by‐step usage of ConVarT. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Searching matching variants (MatchVar) with gene/protein identifiers. Basic Protocol 2 : Searching with a FASTA sequence. Alternate Protocol : Search with gene name in multiple species. Basic Protocol 3 : Search genes associated with a disease.